Ave / Eva: a Brief Approach of the Female Universe in the Cantigas de Santa Maria - Botana Vilar, María Jesús (Madrygal. Revista de Estudios Gallegos, 2020)
The canonical female model that appears in the Cantigas de Santa Maria responds to the idea of the classic Ave / Eva paronomasia. María-Ave symbolizes, on the one hand, the αειπαρθένος (‘always Virgin’) and the Παναϒία, (‘all holy’), the woman that the troubadour chooses to express his love and that is projected as a model of behavior because she is unique among all the others; and on the other hand, Eve, who, as the creator of original sin and epitome of arrogance and weakness, represents the rest of women. Mary is an open door, Eva is condemnation.
Keywords: Cantigas de Santa Maria; Ave / Eva paronomasia; women in the cantigas; female universe